Prinsip Tauhid Dalam Pendidikan Keluarga Dalam Surah Luqman - Sahibul Ardi (An-Nahdhah | Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2021)
This paper presents one of the principles in family education that must be adhered by parents as the first educators for children, namely monotheism principle, that as the main basis that must be emphasized in family education. This paper aims to provide an overview of Surah Luqman verse 13 and its relation to the principle of monotheism in family education. literature study used as series of processes related to literacy by collecting library data with descriptive analysis of the verses of the Qur'an, Surah Luqman verse 13. In this verse it clearly shows how Luqman educated his children to not to associate Allah with other ones. The contents of surah Luqman verse 13 relate to monotheism principle in family education, that important role in Islamic family education. Thus, Parents as educators must be adamant in order to have mature children who have faith, have noble character and have good future, because faith is the foundation of every human action.